A road traffic simulator with parallel process ability - Handoko, D.; Sediono, Wahju; Gunawan, M. (LIPI Press, 2006)
Traffic jam is a common view in big cities in Indonesia. In order to obtain an optimal traffic rules to decrease the traffic jam, a traffic simulator tool is required. A microscopic road traffic simulator core for simulating behavior of road traffics have been designed and developed in this study. The model for vehicles movement is developed based on behavioral model. In the simulator, the simulation is performed based on lane by lane. The core has also the ability to analyze the vehicle flow rate of the lane. The core has also the ability to analyze the vehicle flow rate of the lane. A road traffic simulation in a large area often required in order to see the effect of traffic rules changing in more wide area. However, for a large road traffic area simulation a large computing power is required, therefore consideration of parallel porting of the program structure is required. The computer program design and the strategy for parallel porting of the program will be described in this paper.